Sexual and gender-based violence: the case for transformative justice in Cambodia. Issue 3 (2nd September 2019) - Szablewska, Natalia; Jurasz, Olga
ABSTRACT: This article aims to advance the idea of transformative justice by building on and expanding the notion of 'justice' beyond that traditionally offered by transitional justice discourse and practice. The need for a paradigm shift is warranted by the continued high levels of sexual and gender-based violence (SGBV), directed predominantly towards women, experienced in post-conflict contexts. Using the example of Cambodia, we argue that the scale of SGBV in a post-conflict country can be an indicator of the extent of 'transformative' change taking place, and, thus, of the success of transitional justice processes and democracy consolidation, particularly regarding gender equality. Gender equality is essential for democratisation, as democracy should be both a political and a social project. Thus, democracy- and peace-building efforts require challenging entrenched power hierarchies and deep-rooted gender inequality, of which SGBV is symptomatic.